Comparative analysis of combined exercise programs in middle-aged obese males: impact on energy expenditure, body composition, and metabolic rate - Grivas, Gerasimos V. (Frontiers in Sports and Active Living, 2025)
IntroductionThis study compares energy expenditure, body composition, and metabolic rate between serial (SCG) and integrated (ICG) combined training in untrained middle-aged obese males. Method: Twenty untrained obese males (age: 50 ± 3 years) were randomly assigned to a SCG (n = 10) or an ICG (n = 10). Both groups completed a 3-month training program (3 sessions/week) consisting of walking and bodyweight exercises, differing only in the sequence of aerobic and strength training. In SCG, strength training was performed before aerobic training, while in ICG, aerobic and strength exercises alternated in a predetermined order.ResultsAfter a 3-month training period, both groups significantly improved all health indices compared to pre-training values (p < 0.005, g = 0.40–2.71), indicating small to large effects. Specifically, there were moderate reductions in body fat percentage, small decreases in body circumferences, and moderate-to-large reductions in arterial blood pressure and resting heart rate. Additionally, respiratory function showed a large improvement. No significant differences were observed between SCG and ICG in energy expenditure, resting metabolic rate, total daily energy expenditure, macronutrient composition, or health indices after the intervention (p > 0.05).ConclusionIn conclusion, both SCG and ICG are effective strategies for improving metabolic health, respiratory function, and body composition in middle-aged obese males. These findings highlight the flexibility of combined training approaches in promoting overall health and fitness in this population and suggest that both combined training programs can be implemented in structured exercise programs to promote cardiometabolic health in middle-aged adults.